2018
DOI: 10.1039/c7ra10830c
|View full text |Cite
|
Sign up to set email alerts
|

Wear and corrosion resistance of Co–P coatings: the effects of current modes

Abstract: The P content in the Co–P coatings increased in the sequence of DC, PC and PRC methods. The PRC Co–P coating has better wear and corrosion resistance than DC and PC Co–P coatings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Moreover, the formed small pyramidal grains in the microstructure of this deposit can give rise to surface roughness. Apart from the effects of embedded reinforcements on the R a of Co-P deposits, Li et al [40] indicated that the employed current mode can significantly alter the R a of Co-P coatings. While the pulse reverse current (PRC) provides the highest R a , the surface roughness of coatings obtained by a direct current (DC) is the lowest.…”
Section: Tafel Polarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the formed small pyramidal grains in the microstructure of this deposit can give rise to surface roughness. Apart from the effects of embedded reinforcements on the R a of Co-P deposits, Li et al [40] indicated that the employed current mode can significantly alter the R a of Co-P coatings. While the pulse reverse current (PRC) provides the highest R a , the surface roughness of coatings obtained by a direct current (DC) is the lowest.…”
Section: Tafel Polarizationmentioning
confidence: 99%
“…Therefore, if the aim was to assess the corrosion performance of a deposit, the influences of other factors should also be taken into account; (3) surface roughness; higher surface roughness degrades the corrosion behavior of a coating. Published papers in this field have showed better corrosion behavior of Co-P coatings with a smooth surface than of those with higher roughness because of the greater heterogeneity of the rougher surface facilitating the corrosion attacks [17,40] ; (4) matrix characteristics; this factor becomes more pronounced when using alloy matrix composite coatings such as Ni-P and Co-P. In these coating systems, the amount of phosphorous can markedly change the corrosion properties.…”
Section: Corrosion Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Electrodeposition is a facile process for obtaining MG coatings that is attractive because of its simplicity, rapid deposition rate, cost-effectiveness, low-temperature operation, and tuning of composition with enhanced surface properties. Here, biocompatible Co–P metallic glass coatings were synthesized by a facile electrodeposition approach, and their tribological behavior was evaluated in a simulated physiological environment. There are several studies on the microstructure and wear behavior of Co–P alloys with varying phosphorus content. However, there are no reports related to their biocompatibility and performance in a physiological environment. Here, we systematically investigated the tribological response, mechanical properties, and biocompatibility of Co 100– x P x ( x = 10 and 20 at.…”
Section: Introductionmentioning
confidence: 99%
“…The electrodeposition technique has been accepted as an effective and efficient method to prepare Co-P coating and to regulate the coating performance. The physicochemical properties of electrodeposited Co-P coatings therefore have been studied by many researchers [5][6][7]. For instance, Kosta et al comparatively investigated the electrodeposited Co-P coating and EHC coating, obtaining a homogenous coating with the encouraging corrosion resistance of Co-P coatings [4].…”
Section: Introductionmentioning
confidence: 99%